The Tedak Siten Tradition in Islamic Educational Values Perspective - Nur Machmud Abdullah; Imam Syafe'i (Journal of Research in Islamic Education, 2022)
This research is a custom object off the ground for Javanese conducted by the public in Sumbersari, East Lampung. The approach used is descripive qualitative data collection techniques such as interviews, observation, and documentation. Validation data using triangulation techniques and to analyze the data through several stages, namely: data collection, data reduction, data display, and then the data conclusions by looking back at the data that has been collected. The results showed that the tedak sinten (customary land down) since time immemorial have been made of their ancestors and continue to this day, they are considered custom picture off the ground known as the child’s talents or interests that relate man to God Almighty to always tangible safety, protection, peace, and prosperity in life. Furthermore, the results of the analysis of the study stated that the tedak siten in Sumbersari did not break the Islamic law. Therefore if there are irregularities in the implementation of the Islamic law, then they should not be implemented custom not to be involved in the case of shirik or ignoring Alloh Almighty.